Optimizing Positive e-Word of Mouth: Unveiling the Influence of Brand Personification, Social Presence, and Message Characteristics - Kussusanti, Kussusanti; Gunawan, Imsar (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Several companies aim to enhance digital marketing communication processes to achieve desired outcomes. Strategies include brand personification, embodying a human persona for the brand, and fostering social presence, perceived through communication activities. The characteristics of the message also play a significant role. However, research on the role of brand personification, social presence, and message characteristics on Instagram remains scarce. This study investigates their influence on positive e-word-of-mouth intention within Indonesia's telecommunication service provider industry.  A quantitative research method is employed, using Structural Equation Modeling (SEM) with the Lisrel program for data analysis from 254 respondents, findings indicate significant effects. Brand personification, social presence, and message characteristics positively impact e-word-of-mouth intention, with respective influences of 0.17, 0.27, and 0.40. The study suggests telecommunication companies leverage these factors to cultivate positive e-word-of-mouth intention among customers, aiding in digital marketing effectiveness.